Atrial pacing and administration of nifekalant hydrochloride for unstable atrial fibrillation: a case report. Issue 3 (14th May 2020) - Yakabe, Daisuke; Araki, Masahiro; Furukawa, Kojiro; Nakamura, Toshihiro
Abstract: Background: Atrial fibrillation (AF) is a common arrhythmia in patients with hypertrophic cardiomyopathy (HCM) and can deteriorate haemodynamic status. Case summary: We report a case of a 77-year-old woman with cardiogenic shock due to paroxysmal AF, complicated with HCM and aortic stenosis. Atrial fibrillation was successfully managed with temporary atrial pacing and administration of nifekalant hydrochloride without invasive mechanical circulatory support until surgery. Septal myectomy, aortic valve replacement, and pulmonary vein isolation were performed. Discussion: This case suggests that atrial pacing and nifekalant may be safe and effective for rhythm control.